2002
DOI: 10.1034/j.1600-051x.2002.290101.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine varnishes: a review

Abstract: Clinical reports on the efficacy of controlled-release systems in altering cariogenic and periodontopathic microflora are summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 56 publications
2
87
0
11
Order By: Relevance
“…With regard to S. mutans levels, the largest reduction was also observed in group G2 (CHX + XYL) (91.3%), whereas group G3 (CHX) had 85.9%, a value close to that from G1 (XYL) (91.3%). These results support other previous studies 3,26,28 which showed that individuals using chlorhexidine had the best results regarding biofilm reduction compared to those using either fluoride or only xylitol (G4 and G1, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With regard to S. mutans levels, the largest reduction was also observed in group G2 (CHX + XYL) (91.3%), whereas group G3 (CHX) had 85.9%, a value close to that from G1 (XYL) (91.3%). These results support other previous studies 3,26,28 which showed that individuals using chlorhexidine had the best results regarding biofilm reduction compared to those using either fluoride or only xylitol (G4 and G1, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…3,4,26,29 In our study, we observed that in those groups where chlorhexidine was one of the agents (G2 and G3), the levels of S. mutans continued to decrease even during the three month interval between the second and sixth month evaluations. This finding confirms its substantivity.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…However, this side effect can be eliminated with the use of local CHX varnish application 29 . In the selected articles, different concentrations of CHX varnishes were used.…”
Section: Discussionmentioning
confidence: 99%